Estimating HIV Incidence during Pregnancy and Knowledge of Prevention of Mother-to-Child Transmission with an Ad Hoc Analysis of Potential Cofactors - Thomas Obinchemti Egbe; Rose-Mary Asong Tazinya; Gregory Edie Halle-Ekane; Eta-Nkongho Egbe; Eric Akum Achidi (Journal of Pregnancy)
Background. We determined the incidence of HIV seroconversion during the second and third trimesters of pregnancy and ad hoc potential cofactors associated with HIV seroconversion after having an HIV-negative result antenatally. We also studied knowledge of PMTCT among pregnant women in seven health facilities in Fako Division, South West Region, Cameroon. Method. During the period between September 12 and December 4, 2011, we recruited a cohort of 477 HIV-negative pregnant women by cluster sampling. Data collection was with a pretested interviewer-administered questionnaire. Sociodemographic information, knowledge of PMTCT, and methods of HIV prevention were obtained from the study population and we did Voluntary Counselling and Testing (VCT) for HIV. Results. The incidence rate of HIV seroconversion during pregnancy was 6.8/100 woman-years. Ninety percent of the participants did not use condoms throughout pregnancy but had a good knowledge of PMTCT of HIV. Only 31.9% of participants knew their HIV status before the booking visit and 33% did not know the HIV status of their partners. Conclusion. The incidence rate of HIV seroconversion in the Fako Division, Cameroon, was 6.8/100 woman-years. No risk factors associated with HIV seroconversion were identified among the study participants because of lack of power to do so.